1982
DOI: 10.1093/ajcn/35.6.1459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drinking water and total sodium intake on blood pressure

Abstract: A cohort of 295 persons from a rural area of Michigan were studied to determine if a relationship exists between high levels of sodium in drinking water and blood pressure. Sodium in drinking water, dietary sodium intake, blood pressure, sodium excretion, height, and weight were measured. No significant relationships between daily mean sodium dietary intake, drinking water sodium, or sodium index (amount of drinking water sodium related to diet sodium intake), and mean blood pressure levels were found. A stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…This was raised originally in relation to hypertension in both children and adults, although it was thought to be unlikely, even in areas where a higher sodium content of drinking water was observed [21][22][23]. Subjects with AF can be extremely sensitive to the effects of pressor substances or electrolytes, which was the basis of the successful use of sea water (albeit with a considerably higher sodium content) to reduce orthostatic hypotension in one such subject [24].…”
Section: Discussionmentioning
confidence: 99%
“…This was raised originally in relation to hypertension in both children and adults, although it was thought to be unlikely, even in areas where a higher sodium content of drinking water was observed [21][22][23]. Subjects with AF can be extremely sensitive to the effects of pressor substances or electrolytes, which was the basis of the successful use of sea water (albeit with a considerably higher sodium content) to reduce orthostatic hypotension in one such subject [24].…”
Section: Discussionmentioning
confidence: 99%
“…Nine of the urinary sodium studies, reported in 7 papers and ranging in sample size from 72 to 322, did not control for other factors [14 -20]. Six of the 9 studies (reported in 5 papers) found no significant associations between urinary sodium and BP [6,14,15,17,18], whereas the other 3 found significant positive associations between urinary sodium and either SBP [16,19] or mean BP [20].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, with the use of overnight rather than spot urine collections to characterize sodium intake, six*" 43 …”
mentioning
confidence: 99%